Association between circulating cytokine levels, diabetes and insulin resistance in a population‐based sample (CoLaus study). (7th January 2013) - Marques‐Vidal, Pedro; Bastardot, François; von, Roland; Paccaud, Fred; Preisig, Martin; Waeber, Gérard; Vollenweider, Peter
Summary Objective The associations between inflammation, diabetes and insulin resistance remain controversial. Hence, we assessed the associations between diabetes, insulin resistance (using HOMA‐IR) and metabolic syndrome with the inflammatory markers high‐sensitive C‐reactive protein (hs‐CRP), interleukin‐1 beta (IL‐1β), interleukin‐6 (IL‐6) and tumour necrosis factor‐α (TNF‐α). Design Cross‐sectional study. Participants Two thousand eight hundred and eighty‐four men and 3201 women, aged 35–75, participated in this study. Methods C‐reactive protein was assessed by immunoassay and cytokines by multiplexed flow cytometric assay. In a subgroup of 532 participants, an oral glucose tolerance test (OGTT) was performed to screen for impaired glucose tolerance (IGT). Results IL‐6, TNF‐α and hs‐CRP were significantly and positively correlated with fasting plasma glucose (FPG), insulin and HOMA‐IR. Participants with diabetes had higher IL‐6, TNF‐α and hs‐CRP levels than participants without diabetes; this difference persisted for hs‐CRP after multivariate adjustment. Participants with metabolic syndrome had increased IL‐6, TNF‐α and hs‐CRP levels; these differences persisted after multivariate adjustment. Participants in the highest quartile of HOMA‐IR had increased IL‐6, TNF‐α and hs‐CRP levels; these differences persisted for TNF‐α and hs‐CRP after multivariate adjustment. No association was found between IL‐1β levels and all diabetes and insulin resistance markers studied. Finally, participants with IGT had higher hs‐CRP levels than participants with a normal OGTT, but this difference disappeared after controlling for body mass index (BMI). Conclusion We found that subjects with diabetes, metabolic syndrome and increased insulin resistance had increased levels of IL6, TNF‐α and hs‐CRP, while no association was found with IL‐1β. The increased inflammatory state of subjects with IGT is partially explained by increased BMI.